Aristotle’s Μετεωρολογικά: Meteorology then and now - Riccardo Pozzo (Proceedings (European Academy of Sciences and Arts))
This most recent English commented translation of Aristotle’s Metereologica focuses on how Aristotle’s treatise compares with our understanding of meteorology and climate change. In their extensive commentaries, the editors explain how Aristotle tried to explain weather 2.300 years ago, having at his disposal only logic, eye observation, past experience, and primitive instrumentation. The book uses telling examples and can be easily followed by general readers.